Respuesta :

Answer:

16x^3 + 8x^2 + 12x

Step-by-step explanation:

Given the product 4x(x^2+2x+3)

On Expanding

4x(x^2+2x+3)

= 4x(x^2)+4x(2x)+4x(3)

=  16x^3 + 8x^2 + 12x

Hence the Area of the model is 16x^3 + 8x^2 + 12x

The area model is as follows:

4x × (x²) = 4x³

4x × (2x) = 8x²

4x × (3) = 12x

The area model that will be use to multiply 4x(x² + 2x +3) is as follows:

  • 4x(x² + 2x +3)

4x × (x²) = 4x³

4x × (2x) = 8x²

4x × (3) = 12x

Therefore,

4x(x² + 2x +3)  = 4x³ + 8x² + 12x

learn more on area model here: https://brainly.com/question/2281913